Architectural and Urban Design of Public Space Based on Social Cooperation - Lewandowska, Agnieszka (Journal of Education Culture and Society, 2018)
AimThe subject of this work are contemporary methods of designing public space based on cooperation with city users. At present, authorities of the cities attempt to involve citizens in the process of architectural change. The key component of the series of research are designing processes composed of various social consultations, architectural workshops and competitions, in which the resident's need to shape the city is visible and evident.MethodsThe author of article will indicate varied methods of designing public space involving citizens, based on experiences of Warsaw (Poland), and conducted analysis of design processes and results.Results and ConclusionArchitecture is a reflection of political and economic situation but is also a reflection of citizens way of living. The gap between city users and professionals might be filled with social cooperation process. The residents knowledge of the space is essential to build and transform the cities in a way to fulfill the user’s needs and requirements.